Peningkatan Pelaksanaan Pembelajaran Tematik Menggunakan Model Problem Based Learning Kelas IV SD Negeri 34 - Yolanda Rahma Sari; Mai Sri Lena (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This study aimes to describe the increase in the implementation n by using problem based learning (PBL) mode.This study approach which are qualitative an quantitative. This type of research is class action. This research was conducted at 34 Public Elementary School, Air Pacah, Padang City. The results showed there were 1. the assessment of planning for implementation in cycle 1 75% and then to increase 93.75% in cycle 2.observation on teachers aspects in cycle 1 78.57% and the observation on teachers aspects in cycle 2 of 92.85%. on the  skills aspect of cycle 1 76.29% and in the aspects of the second cycle 85.5%.